2020
DOI: 10.1504/ijcg.2020.107404
|View full text |Cite
|
Sign up to set email alerts
|

Capital contribution, insider ownership and firm performance: evidence from Indian IPO firms

Abstract: Several studies have explored the nonlinear relationship between insider ownership and post-IPO firm performance, whereas the inter-relationship among pre-IPO cash contribution, insider ownership and firm performance has not been investigated. Our study attempts to do so for an emerging economy, India using panel data of 199 IPO firms for the sample period of 2007 to 2018. Results indicate that there is a nonlinear relationship between insider ownership and post-IPO firm performance with lower ownership levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In a longitudinal study on Indian IPOs, Singh et al (2020) found that from 1991 onwards, the amount of IPO capital grew at a rate of 11.54% compounded annually, while the number of IPO issues declined at a rate of 9.91% compounded annually. The average size of IPOs has increased by 21.46% annually (Jain et al , 2020).…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In a longitudinal study on Indian IPOs, Singh et al (2020) found that from 1991 onwards, the amount of IPO capital grew at a rate of 11.54% compounded annually, while the number of IPO issues declined at a rate of 9.91% compounded annually. The average size of IPOs has increased by 21.46% annually (Jain et al , 2020).…”
Section: Background Of the Studymentioning
confidence: 99%
“…The underpricing level of SME IPOs is also lower than that of the IPOs listed in other board of stock exchanges (Dhamija and Arora 2017c). Poor long run performance after the IPO event can be due to large insider ownership (Jain et al , 2020). IPO firms from banking sector have witnessed higher performance in post listing period (Ghosh 2005a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the expanding literature investigates the impact of institutional (Suto & Toshino, 2005;Kabir et al, 2020), foreign (Ahmadjian & Robbins, 2005;Nagaoka, 2006;Sueyoshi, Goto, & Omi, 2010) and concentrated ownership (Nguyen, 2011) on firm risk-taking. In addition, the extant literature provides evidence on the impact of insider ownership on firm performance (Iturralde, Maseda, & Arosa, 2011;Jain, Gunasekar, & Balasubramanian, 2020). However, the impact of insider ownership on default risk remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%